SHORT-TERM BIOEFFECTS OF EXTRACORPOREAL SHOCKWAVE LITHOTRIPSY - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1994)
Safety guidelines for shockwave delivery during extracorporeal shockwave lithotripsy (SWL) are not yet clear. Renal functions were assessed by using urinary N-acetyl-beta-D-glucosaminidase (NAG), lactate dehydrogenase (LDH), alanine aminotransferase (ALT; EC.2.6.1.2), aspartate aminotransferase (AST; EC. 2.6.1.1), and gamma-glutamyltransferase (GGT) as well as sodium, potassium, and calcium concentrations in respect to tubular functions after SWL with the Dornier MFL 5000 unit in 32 patients. In order to monitor glomerular function, we determined microalbuminuria. Transient glomerular and tubular damage occurs in SWL-treated kidneys. The minimum interval between two shockwave treatments should be at least 7 days.
Keywords: WAVE LITHOTRIPSY; RENAL-FUNCTION; EXCRETION; KIDNEY; DAMAGE; STONES; EXPOSURE; ENZYMES